Let $a,b,$ and $c$ be positive numbers with $a+b+c = 1$. Prove that $$\left (\dfrac{1}{a}+1 \right)\left (\dfrac{1}{b}+1 \right)\left (\dfrac{1}{c}+1 \right) \geq 64.$$


Expanding the LHS we obtain $\left (\dfrac{1+a}{a} \right)\left (\dfrac{1+b}{b} \right)\left (\dfrac{1+c}{c} \right)$. We are given that $a+b+c = 1$, so substituting that in we get $\left (\dfrac{b+c+2a}{a} \right)\left (\dfrac{a+c+2b}{b} \right)\left (\dfrac{a+b+2c}{c} \right)$. Then do I say $\left (\dfrac{b+c+2a}{a} \right)\left (\dfrac{a+c+2b}{b} \right)\left (\dfrac{a+b+2c}{c} \right) \geq 64$ and see if I can get a true statement from this?


Use the AM GM inequality : $$a+a+b+c\geq 4(a^2bc)^\frac{1}{4}$$ $$a+b+b+c\geq 4(ab^2c)^\frac{1}{4}$$ $$a+b+c+c\geq 4(abc^2)^\frac{1}{4}$$ Multiply the three inequalities and then divide $abc$ on both sides to get the desired inequality.


Sheer brute force is adequate:

$$(2a + b + c)(a + 2b + c)(a + b + 2c)$$

$$= 2(a^3 + b^3 + c^3) + 7(a^2b + ab^2 + a^2c+ac^2 + b^2c+bc^2) + 16(abc)$$

$$\geq 2(3abc) + 7(6abc) + 16(abc) = 64abc$$

  • $\begingroup$ Nice solution... $\endgroup$ – qwr Dec 29 '15 at 3:57

Probably, you already got the expected solution (from elementary algebra) in the other answers. So, I will give a different proof (from Multivariable Calculus). Specifically, I will use the Lagrange Multipliers Method to prove the following

Result: Given positive numbers $a$, $b$, $c$ and $d$ with $a+b+c=1$, we have $$\left(\frac{1}{a+d}+1\right)\left(\frac{1}{b+d}+1\right)\left(\frac{1}{c+d}+1\right)\geq\left(\frac{1}{\frac{1}{3}+d}+1\right)^3\tag{$*$}$$

Remark 1: Letting $d\to 0$ in $(*)$, we get $$\left(\frac{1}{a}+1\right)\left(\frac{1}{b}+1\right)\left(\frac{1}{c}+1\right)\geq\left(\frac{1}{\frac{1}{3}}+1\right)^3=64$$ as you want.

Remark 2: The same approach can be used to prove that for any positive numbers $x_1,...,x_n$ with $x_1+\cdots+x_n=c$ we have $$\left(\frac{1}{x_1}+1\right)\left(\frac{1}{x_2}+1\right)\cdots\left(\frac{1}{x_n}+1\right)\geq \left(\frac{n}{c}+1\right)^n$$ (See here the case $n=2$.)

Proof of Result: Let $d>0$ and $U=\{(a,b,c);\;a>0,\;b>0,\;c>0\}$. Define $f:U\to\mathbb{R}$ and $\varphi:U\to \mathbb{R}$ by $f(a,b,c)=\left(\frac{1}{a+d}+1\right)\left(\frac{1}{b+d}+1\right)\left(\frac{1}{c+d}+1\right)$ and $\varphi(a,b,c)=a+b+c$. Then, $$\nabla f(a,b,c)=-\left(\tfrac{1}{A^2}\left(\tfrac{1}{B}+1\right)\left(\tfrac{1}{C}+1\right),\tfrac{1}{B^2}\left(\tfrac{1}{A}+1\right)\left(\tfrac{1}{C}+1\right),\tfrac{1}{C^2}\left(\tfrac{1}{A}+1\right)\left(\tfrac{1}{B}+1\right)\right)$$ where $A=a+d$, $B=b+d$ and $C=c+d$, and $\nabla\varphi(a,b,c)=(1,1,1)$.

It follows from the Lagrange Multipliers Method that:

$$(a,b,c)\in \varphi^{-1}(1)\text{ is a critical point of } f\quad\Longleftrightarrow\quad\nabla f(a,b,c)=\lambda \nabla \varphi(a,b,c) \text{ for some } \lambda\in\mathbb{R}$$ $$\Longleftrightarrow \qquad\frac{1}{A^2}\left(\frac{1}{B}+1\right)\left(\frac{1}{C}+1\right) =\frac{1}{B^2}\left(\frac{1}{A}+1\right)\left(\frac{1}{C}+1\right) =\frac{1}{C^2}\left(\frac{1}{A}+1\right)\left(\frac{1}{B}+1\right)$$ $$\Longleftrightarrow\qquad \left\{ \begin{align}\frac{1}{A^2}\left(\frac{1}{B}+1\right) &=\frac{1}{B^2}\left(\frac{1}{A}+1\right)\\ \frac{1}{A^2}\left(\frac{1}{C}+1\right) &=\frac{1}{C^2}\left(\frac{1}{A}+1\right)\\ \frac{1}{B^2}\left(\frac{1}{C}+1\right) &=\frac{1}{C^2}\left(\frac{1}{B}+1\right)\end{align}\right.$$

$$\Longleftrightarrow\qquad\left\{\begin{align} B+B^2&=A+A^2\\ C+C^2&=A+A^2\\ C+C^2&=B+B^2 \end{align}\right.$$

$$\Longleftrightarrow\qquad\left\{\begin{align} B-A&=A^2-B^2=-(A+B)(B-A)\\ C-A&=A^2-C^2=-(A+C)(C-A)\\ C-B&=B^2-C^2=-(B+C)(C-B) \end{align}\right.$$

$$\Longleftrightarrow\quad A=B=C$$

$$\Longleftrightarrow\quad a=b=c=\frac{1}{3}$$

So, $q=(\frac{1}{3},\frac{1}{3},\frac{1}{3})$ is the unique critical point of $f$ in $\varphi^{-1}(1)$.

The expression of $f(a,b,c)$ defines a continuous function $g$ on $$\overline{\varphi^{-1}(1)}=\{(a,b,c);\;a\geq 0,\;b\geq 0,\;c\geq 0,\;a+b+c=1\}.$$ Since $\overline{\varphi^{-1}(1)}$ is compact, $g$ attains minimum at some point $p=(p_1,p_2,p_3)\in \overline{\varphi^{-1}(1)}$.

If $p\in \overline{\varphi^{-1}(1)}\setminus {\varphi^{-1}(1)}$ then $p_1=0$ or $p_2=0$ or $p_3=0$. Assume $p_1=0$. Then $$\left(\frac{1}{a+d}+1\right)\left(\frac{1}{b+d}+1\right)\left(\frac{1}{c+d}+1\right)\geq \left(\frac{1}{d}+1\right)\left(\frac{1}{p_2+d}+1\right)\left(\frac{1}{p_3+d}+1\right)$$ which is a contradiction (because letting $d\to 0$, the LHS goes to some constant and the RHS goes to $\infty$). It follows that $p_1= 0$ is impossible. The same argument shows that $p_2\neq 0$ and $p_3\neq0$. Therefore, $p\in\varphi^{-1}(1)$. Since $g=f$ on $\varphi^{-1}(1)$, we conclude that $f$ attains minimum in $\varphi^{-1}(1)$. Thus, the minimum value of $f$ in $\varphi^{-1}(1)$ is $f(q)$ (because $q$ is the unique critical point of $f$ in $\varphi^{-1}(1)$).

Therefore, for all $(a,b,c)\in\varphi^{-1}(1)$ we have $$f(a,b,c)\geq f\left(\tfrac{1}{3},\tfrac{1}{3},\tfrac{1}{3}\right)\tag{#}$$ As $(\text{#})$ is $(*)$, the proof is complete. $\Box $


Here is a "simple" proof utilizing GM-HM inequality.

Use GM-HM inequality on the set $\{\frac{a+1}{a},\frac{b+1}{b},\frac{c+1}{c}\} $ to get:

$$\left(\,\left(\frac{a+1}{a}\right)\left(\frac{b+1}{b}\right)\left(\frac{c+1}{c}\right)\,\right)^\frac{1}{3} \geq \frac {3} {\left(\frac{a}{a+1}\right) +\left(\frac{b}{b+1}\right) + \left(\frac{c}{c+1}\right)} $$

$$\implies \,\left(\frac{a+1}{a}\right)\left(\frac{b+1}{b}\right)\left(\frac{c+1}{c}\right) \geq \frac {27} {\left( \,\, \left(\frac{a}{a+1}\right) +\left(\frac{b}{b+1}\right) + \left(\frac{c}{c+1}\right)\,\,\right)^{3}} \,\,\,(♦)$$

Now, maximizing $\left(\frac{a}{a+1}\right) +\left(\frac{b}{b+1}\right) + \left(\frac{c}{c+1}\right)$ according to the constraint $a+b+c=1$ , its maximum value comes out to be $\frac{3}{4}$.

$$\therefore \left(\frac{a}{a+1}\right) +\left(\frac{b}{b+1}\right) + \left(\frac{c}{c+1}\right) \leq \frac {3}{4}\,\,\,(♣)$$

Plug $(♣)$ in $(♦)$ to get :

$$\left(\frac {a+1}{a}\right) \left( \frac{b+1}{b}\right) \left(\frac{c+1}{c}\right) \geq \frac {27} {(3/4)^3} =\frac {27\times 64}{27} = 64$$


$$\left(\frac{1}{a}+1\right)\left(\frac{1}{b}+1\right)\left(\frac{1}{c}+1\right) \geq 64$$

as desired.

$$HENCE \,\,\,\, PROVED$$

  • $\begingroup$ $$\implies \,\big(\frac{a+1}{a}\big)\big(\frac{b+1}{b}\big)\big(\frac{c+1}{c}\big) \geq \frac {27} {\big( \,\, \big(\frac{a}{a+1}\big) +\big(\frac{b}{b+1}\big) + \big(\frac{c}{c+1}\big)\,\,\big)^\color{red}{{\frac{3}{1}}}} \,\,\,(♦)$$ Is this what you mean or I missed something ? $\endgroup$ – A---B Feb 4 '17 at 8:03
  • $\begingroup$ @A---B O yeah you are right.... just a typo .... edit on its way. Thanks for correcting me. $\endgroup$ – user399078 Feb 4 '17 at 8:14
  • $\begingroup$ @A---B How do you rate my answer ???? Is it ok or should I add fine-tune it further ... ???? $\endgroup$ – user399078 Feb 4 '17 at 8:15
  • $\begingroup$ It is good but if you have time you can use \left and \right to make brackets of apropriate size. like $({3 \over 2})$ becomes $\left({3 \over 2}\right)$. $\left({3 \over 2}\right)$ $\endgroup$ – A---B Feb 4 '17 at 12:48
  • $\begingroup$ @A---B Thanks for the suggestion ! :) $\endgroup$ – user399078 Feb 4 '17 at 12:54

Probably you mean $a,b,c\geq 0$. You want to find the miminmum of $$\ln (1+\frac{1}{a})+\ln(1+\frac{1}{b})+\ln(1+\frac{1}{1-a-b})$$ for $a,b\geq 0$. The partial derivatives are zero iff $$ -\frac{1}{a(a+1)}+\frac{1}{(1-a-b)(2-a-b)}=0 $$ and a similar equation in which $a$ and $b$ will be replaced. By subtracting, you get $a(a+1)=b(b+1)$ which implies (given that all is positive) $a=b$. But that's the minimum, $a=b=c=1/3$.


By AM-GM we have:

$1 + \frac{1}{a} = \frac{1}{a}(a + b + c + a) \ge \frac{1}{a}4\sqrt[4]{{{a^2}bc}}$

$\Rightarrow 1 + \frac{1}{a} \ge \frac{4}{a}\sqrt[4]{{\frac{{{a^4}bc}}{{{a^2}}}}} = 4\sqrt[4]{{\frac{{bc}}{{{a^2}}}}} $

And $1 + \frac{1}{b} \ge 4\sqrt[4]{{\frac{{ca}}{{{b^2}}}}};1 + \frac{1}{c} \ge 4\sqrt[4]{{\frac{{ab}}{{{c^2}}}}}$

$$\Rightarrow \left( {1 + \frac{1}{a}} \right)\left( {1 + \frac{1}{b}} \right)\left( {1 + \frac{1}{c}} \right) \ge 4\sqrt[4]{{\frac{{bc}}{{{a^2}}}}}4\sqrt[4]{{\frac{{ca}}{{{b^2}}}}}4\sqrt[4]{{\frac{{ab}}{{{c^2}}}}} = 64$$


We need prove: $(1+a)(1+b)(1+c) \geq (1+\sqrt[3]{abc})^3$

$\Leftrightarrow 1+abc+ab+bc+ca+a+b+c \geq 1+3\sqrt[3]{(abc)^2}+3\sqrt[3]{abc}+abc$

$\Leftrightarrow ab+bc+ca+a+b+c \geq 3\sqrt[3]{(abc)^2}+3\sqrt[3]{abc}$

Right by AM-GM. Apply we have:

$\left(1+\frac{1}{a} \right)\left(1+\frac{1}{b} \right)\left(1+\frac{1}{c} \right)=\dfrac{(1+a)(1+b)(1+c)}{abc} \geq \dfrac{(1+\sqrt[3]{abc})^3}{abc} \geq 64$

From $a+b+c=1 \Rightarrow abc\le \frac{1}{27}$

$$\Rightarrow \dfrac{(1+\sqrt[3]{abc})^3}{abc}=\bigg(\dfrac{1}{\sqrt[3]{abc}}+1\bigg)^3 \geq 64$$

When $a=b=c=\dfrac{1}{3}$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.